Designing a Pocket Book to Support Healthy Living in Islamic Boarding School Communities - Sari, Puspita; Helmi Suryani Nasution; Marta Butar Butar; Solihin Sayuti (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: One of the efforts to prevent health problems in students in Islamic boarding schools is by building awareness to carry out clean and healthy living behavior (PHBS). Efforts to introduce and improve students' knowledge can be done by using health education media in the form of pocket books. Objective: To produce a PHBS pocket book for students in Islamic boarding schools. Methods: This study uses the RnD approach based on the ADDIE Model (Analyze, Design, Development, Implementation, and Evaluation). The media was validated by expert media validators, language experts, public health practitioners, agency validators, and students in grades X and XI of the Ar-Rahman Islamic Boarding School. Data collection used literature studies and data were analyzed manually. Results: The development of the PHBS pocket book in Islamic Boarding Schools began with identifying potential problems and, collecting data, and information. Product design creation using the Ibis Paint X application. The product obtained validation results, namely media experts of 96% (very feasible), language experts of 92% (very feasible), public health practitioners of 99% (very feasible), validation of institutions consisting of teachers of 100% (very feasible). After receiving suggestions and comments from the validator, the product was then revised. Then the results of the product trial on the participant group were 88% (very feasible) Conclusion: The PHBS pocket book in Islamic Boarding Schools can be used as a health education media with a very feasible feasibility test. Suggestion: Pocket books can be digitized based on Android.